Chemical changes and optimisation of acetous fermentation time and mother of vinegar concentration in the production of vinegar-like fermented papaya beverage - Kong, Ching Ting; Ho, Chin Wai; Ling, Alvin Jin Wei; Azwan Lazim,; Shazrul Fazry,; Lim, Seng Joe (Penerbit Universiti Kebangsaan Malaysia, 2018)
Fermentation has been long used as a method to produce beverage of various health benefits. In this research, ripe papaya (Carica papaya) was fermented through alcoholic fermentation using Saccharomyces cerevisiae, followed by acetous fermentation using Acetobacter spp. from mother of vinegar, to reduce wastage of this highly perishable Malaysian fruit. The papaya juice was pasteurised prior to the fermentation process. Optimisation of acetous fermentation was carried out using the response surface methodology (RSM) with central composite rotatable design (CCRD). Acetous fermentation time had shown significant effect on all the chemical characteristics while mother of vinegar concentration did not significantly effect on all the chemical characteristics. The vinegar-like fermented papaya beverage which was produced at the optimum point (Fermentation time = 70.80 h and concentration = 40% mother of vinegar) contained 0.37 ± 0.01% reducing sugar, 3.54 ± 0.36% ethanol, 2.46 ± 0.07% acetic acid, 327.89 ± 3.60 mg GAE/ L total phenolic, 2.32 ± 0.17 mg/100 mL ascorbic acid and 52.40 ± 0.23% mg AA/100 mL free-radical scavenging activity. In conclusion, vinegar-like fermented papaya beverage was successfully produced and its chemical compositions changed from papaya juice to wine and vinegar-like beverage with increased bioactive compounds and antioxidative activity.